The feasibility of making the building structures based on the structural simplifications of the human lumbar spine (L3/L4). Issue 13 (13th May 2022) - Salsabili, Neda; Santiago López, Joaquín; Prieto Barrio, Maria Isabel; Esteki, Ali
Abstract: Static and dynamic behaviors of the human spine in response to internal and external loads may be useful in future building design. The new structure was made by simplification in structure parts more than the previous validated material simplifications of Finite Element (FE) of one motion segment of the human lumbar spine (L3/L4). The study showed the anatomical and mechanical properties of this model were adapted to validated previously models by having fewer materials and stress amount. This validated simplified structure by having the natural process may be useful to achieve adaptable, sustainable, and sensible future structures for several disciplines. Highlights: Simplification of human lumbar spine structure more than material simplifications. Simplified lumbar structure for prosthesis, implants, building joints & structures. Having fewer materials, less stress & simple form by simplifying lumbar structure. Simplified lumbar structure by being resistant against internal & external response. Sustainable, sensible & adaptable structure by inspiration of the natural process.